Lessons from PL/I: A Most Ambitious Programming Language: PL/I stands for Programming Language 1, and its aim was to be the Highlander of programming languages. - Meil, Doug (Communications of the ACM, 2023)
The article focuses on PL/I, which stands for Programming Language 1, and how its ambitious goals as a programming language. The author discusses the design of PL/I by International Business Machines (IBM) and explains how it brings together their three programming languages FORTRAN (1954), ALGOL (1958), and COBOL (1959).